Development of a tool to aid the radiologic technologist using augmented reality and computer vision. - MacDougall, Robert D.; Scherrer, Benoit; Don, Steven (Pediatric Radiology, 2018)
This technical innovation describes the development of a novel device to aid technologists in reducing exposure variation and repeat imaging in computed and digital radiography. The device consists of a color video and depth camera in combination with proprietary software and user interface. A monitor in the x-ray control room displays the position of the patient in real time with respect to automatic exposure control chambers and image receptor area. The thickness of the body part of interest is automatically displayed along with a motion indicator for the examined body part. The aim is to provide an automatic measurement of patient thickness to set the x-ray technique and to assist the technologist in detecting errors in positioning and motion before the patient is exposed. The device has the potential to reduce the incidence of repeat imaging by addressing problems technologists encounter daily during the acquisition of radiographs.